التخطيط اللغوي وعلاقته بالسياسة اللغوية بحث في المصطلح والإجراء - عطاالله, محمد (جامعة الوادي - university of Eloued, 2020)
موضوع هذا المقال التخطيط اللغوي والسياسة اللغوية في البلاد العربية مفهوما وتصورا وتجريبا، محددين أنماط السياسة اللغوية فيها وآليات تطبيقها، ودور أصحاب القرار فيها، مبرزين المقومات والمنطلقات الداعمة لرسم تلك السياسة، والنظر في علاقتها بالتخطيط اللغوي بأنواع المختلفة في تجارب الدول المتقدمة في تدبير الشأن اللغوي، ومحاولة إسقاطه على واقع التخطيط والسياسة اللغويتين في البلاد العربية. In this article, we have introduced the language policy adapted by Arab countries, in both constitution and reality. We determined types of language policies and application mechanisms . We also revealed curtain on the role of decision makers , showing supports for the map of that policy . During our work ,we mentioned obstacles and challenges facing the real application of an efficient langauage policy and the ways to overcome such challenges . In the end , we recommended some mechnaisms to activate language policy in the arab countries.
مقال
Keywords: التخطيط ; السياسة ; العلاقة ; المصطلح ; الإجراء